How to Use ETI Drill Downs to Map Employment Integration and to Assess Workforce Diversity at Government Jobsites - (:unkn) unknown (My University, 2005)
While many studies have focused on disparities in employment and earnings of African Americans and Hispanics compared to white workers in the Milwaukee labor force, these reports have not drilled down to a neighborhood or jobsite level where changes can be effected in recruitment, hiring and promotion decisions. This report uses place-of-work data from the 2000 U.S. Census, released in 2004 and 2005 and designed for transportation planners, to assess and compare employment patterns by race/ethnicity at the census tract and block group and by industry, occupation, and type of employer. Racial integration and diversity standards are applied, based on the 80 percent availability rule utilized by the U.S. Equal Employment Opportunity Commission (EEOC) and the Office of Federal Contract Compliance Programs (OFCCP) for the enforcement of anti-discrimination laws and affirmative action requirements placed on federal contractors. This study is the fourth in a series of report cards on hiring practices and challenges in the Milwaukee area.
Keywords: affirmative action; African Americans; Hispanics; diversity